Innovative Aspect of E-Commerce Development in Ukraine - Gamova, Iryna; Гамова, Ірина; Shportiuk, Nataliia; Шпортюк, Наталія Леонідівна; Duginets, Ganna; Дугінець, Ганна; Busarieva, Tatiana; Бусарєва, Тетяна (Одеський торговельно-економічний інститут, 2024)
Introduction. The share of e-trading in the total volume of the Ukrainian retail sales market tends to increase. Since innovative trade approaches open new perspectives and provide the possibility of doing business in conditions of significant challenges, the role of e-commerce in restoring the country's economy becomes more significant. The social role of e-commerce as a source of vital goods for a population is also growing. Therefore, the study of the e-commerce market and analysis of the impact of war on its development have become important tasks. Aim and tasks. The purpose of this study is to examine the state of the e-commerce market using statistical data, analyze the impact of the war on the development of e-commerce, identify the main market trends, and forecast the main indicators of e-commerce. This determines the following tasks: establishing the peculiarities of the e-commerce market in Ukraine, establishing obstacles to the development of e-commerce, identifying opportunities that e-trading opens up for Ukrainian entrepreneurs, and determining the conditions to be taken into account in the transition of retail trade to e-trading under the challenges of war.. Results. The negative impact of significant market changes in the 2022-2023 was compensated by the growth in active e-commerce users. A change in the growth rate of users by 40% in 2022 was confirmed. This indicates that hostilities changed the range of e-commerce products and that the market share of basic necessities exceeded 50%. The highest annual revenue per user for food products will be 89.4% ahead of the product group closest to this indicator. According to the indicator “Average income from e-commerce per client”, it is predicted to reach 2019 only in 2026. Sales changes for the main product groups in 2024 have been established. According to the “Highest annual revenue per user” indicator, food products will exceed the value for 2023 by 25% and personal care products by 9.4%. Conclusions. Innovative technologies (e-marketplace, analysis of buyer profiles, omnichannel communication with consumers, m-trading, etc.) that contribute to the development of e-commerce and the interaction of these technologies and market needs are identified. The peculiarities of the Ukrainian e-commerce market during the war were established. Obstacles to the development of e-commerce and the opportunities that e-trading opens for Ukrainian entrepreneurs have been identified. The conditions that must be considered during the transition from retail trade to e-trading due to the challenges of war, which is especially important for small and medium-sized enterprises, are determined. вступ. Частка електронної торгівлі в загальному обсязі українського ринку роздрібної торгівлі має тенденцію до зростання. Оскільки інноваційні підходи до торгівлі відкривають нові перспективи та забезпечують можливість ведення бізнесу в умовах значних викликів, роль електронної комерції у відновленні економіки країни стає все більш вагомою. Зростає і соціальна роль електронної комерції як джерела життєво необхідних товарів для населення. Тому дослідження ринку електронної комерції та аналіз впливу війни на його розвиток стали актуальними завданнями. Мета і завдання . Метою даного дослідження є вивчення стану ринку електронної комерції за допомогою статистичних даних, аналіз впливу війни на розвиток електронної комерції, визначення основних тенденцій ринку та прогноз основних показників електронної комерції. Це визначає наступні завдання: встановлення особливостей ринку електронної комерції в Україні, встановлення перешкод для розвитку електронної комерції, визначення можливостей, які відкриває електронна торгівля для українських підприємців, визначення умов, які необхідно враховувати при перехід роздрібної торгівлі на електронну торгівлю в умовах війни.. Результати. Негативний вплив значних ринкових змін у 2022-2023 роках було компенсовано зростанням активних користувачів електронної комерції. Підтверджено зміну темпів зростання користувачів на 40% у 2022 році. Це свідчить про те, що військові дії змінили асортимент товарів електронної комерції, а частка ринку товарів першої необхідності перевищила 50%. Найвищий річний дохід на споживача для харчових продуктів становитиме 89,4% випередження найближчої до цього показника групи товарів. За показником «Середній дохід від електронної комерції на одного клієнта» прогнозується досягнення 2019 року лише у 2026 році. Встановлено зміни продажів за основними групами товарів у 2024 році. За показником «Найвищий річний дохід на користувача» продукти харчування перевищать вартість 2023 року на 25%, а засоби особистої гігієни — на 9,4%. Висновки. Визначено інноваційні технології (електронний ринок, аналіз профілів покупців, омніканальна комунікація зі споживачами, м-трейдинг тощо), які сприяють розвитку електронної комерції та взаємодії цих технологій і потреб ринку. Встановлено особливості українського ринку електронної комерції в роки війни. Визначено перешкоди для розвитку електронної комерції та можливості, які електронна торгівля відкриває для українських підприємців. Визначено умови, які необхідно враховувати під час переходу від роздрібної торгівлі до електронної через виклики війни, що особливо актуально для малих і середніх підприємств.
Інноваційний аспект розвитку електронної комерції в Україні
Keywords: e-commerce; електронна комерція; trade; торгівля; innovation; інновації; information and communication technologies; інформаційно-комунікаційні технології; market structure; структура ринку